2022
DOI: 10.3389/fimmu.2022.837457
|View full text |Cite
|
Sign up to set email alerts
|

CD19-Targeted Immunotherapies for Diffuse Large B-Cell Lymphoma

Abstract: Surgical resection, chemotherapy and radiotherapy were, for many years, the only available cancer treatments. Recently, the use of immune checkpoint inhibitors and adoptive cell therapies has emerged as promising alternative. These cancer immunotherapies are aimed to support or harness the patient’s immune system to recognize and destroy cancer cells. Preclinical and clinical studies, based on the use of T cells and more recently NK cells genetically modified with chimeric antigen receptors retargeting the ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…The potential of immunotherapies based on the use of mAbs that target distinct cancer-specific cell markers and may trigger T cell anti-tumor function and NK cell-mediated ADCC has been initially revealed in the hematological setting. Indeed, the successful use of Rituximab, a chimeric anti-CD20 mAb targeting CD20 + lymphoma cells [ 56 , 57 ], has prompted the design of different immune tools to also be applied against solid tumors, including CRC. In this context, several mAbs targeting CRC tumor antigens (e.g., EGFR, CEA, Her2) or the TME (e.g., VEGF) that may simultaneously trigger NK cell cytotoxicity have been developed.…”
Section: Monoclonal Antibodies-based Treatments To Enhance Nk Cell Cy...mentioning
confidence: 99%
“…The potential of immunotherapies based on the use of mAbs that target distinct cancer-specific cell markers and may trigger T cell anti-tumor function and NK cell-mediated ADCC has been initially revealed in the hematological setting. Indeed, the successful use of Rituximab, a chimeric anti-CD20 mAb targeting CD20 + lymphoma cells [ 56 , 57 ], has prompted the design of different immune tools to also be applied against solid tumors, including CRC. In this context, several mAbs targeting CRC tumor antigens (e.g., EGFR, CEA, Her2) or the TME (e.g., VEGF) that may simultaneously trigger NK cell cytotoxicity have been developed.…”
Section: Monoclonal Antibodies-based Treatments To Enhance Nk Cell Cy...mentioning
confidence: 99%
“…CAR-T cells are cytotoxic T cells that have been modified genetically to express an artificial chimeric antigen receptor (CAR). The CAR comprises an extracellular target-binding domain (composed of a single-chain variable fragment (scFv) from antibody light- and heavy-chain variable regions and which bind to the TAA), a spacer/hinge region, transmembrane domains, and intracellular domains (comprising two or more costimulatory domains (CD28 and/or 4-1BB/CD137/TNF-RSF9) and a T cell signaling domain (with CD3ξ) [ 14 , 190 , 191 ]. The first generation of CAR constructs included CD3ξ; the second generation included CD28 and CD3ξ, or 4-1BB and CD3ξ; the third generation included CD28, 4-1BB, and CD3ξ; the fourth generation included a cytokine transgene initiated through NFAT signaling, and the fifth generation included IL-2Rβ (to initiate JAK/STAT signaling) [ 14 , 190 , 191 ].…”
Section: Current Treatments and Clinical Trials Of B Cell Malignancie...mentioning
confidence: 99%
“…The BCR pathway includes a large array of kinases, adaptor proteins and transcription factors (such as NF-κB); in particular, Bruton tyrosine kinase (BTK) and phosphatidylinositol-3 kinase (PI3K) are critical signaling enzymes involved in uncontrolled B cell proliferation and survival [ 10 , 11 , 12 , 13 ] ( Figure 1 b). Lastly, high levels of expression of certain tumor-associated antigens (TAAs; CD19, CD20, CD22, and CD38) in most B cell malignancies are correlated with a high proliferation rate and disease progression ( Table 1 ) [ 14 , 15 , 16 , 17 ]. These TAAs are physically associated with the BCR [ 18 , 19 , 20 , 21 ] and are involved in modulating BCR-dependent ( Figure 1 b) and BCR-independent proliferation/survival signals ( Figure 1 c) [ 13 , 15 , 16 , 17 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Background and Introductionmentioning
confidence: 99%
“…CD19-targeted chimeric antigen receptor (CAR) T-cell therapy has been commercially available for diffuse large B-cell lymphoma (DLBCL) for some years, with perhaps curative potential. 25 A CAR T-cell product was approved for FL in March 2021 based on the phase II ZUMA-5 study of R/R indolent NHL, which showed an ORR of 92.0%, a CR rate of 76.0% and an estimated 12-month duration of response of 72.0%. 26 ZUMA-5 also included 22 patients with R/R MZL.…”
Section: Future Treatment Options For Marginal Zone Lymphomamentioning
confidence: 99%